Comparison of Reaction Wood and Normal Wood of Some Commercial Tree Species - Kaz, Sevinç; Ateş, Saim; Külçe, Tuba (Faculty of Forestry, University of Zagreb, 2023)
This study aims to analyze the reaction wood samples for some industrial tree species naturally grown in Kastamonu province in Turkey and compare them with the relevant standards. Some anatomical, chemical, fiber morphological, optical properties, and color changes before and after drying were analyzed for the reaction wood (RW) samples. While the holocellulose content of fir and pine compression wood (CW) was found to be lesser (~3-4 %), the lignin content was higher than those of the opposite wood (OW) (~34 % for pine and 12 % for fir). On the contrary, the amount of holocellulose was found to be higher (~1-4 %), and the lignin was lower (at about 6-15 %) in the tension wood (TW) samples. It was observed that average lengths are more extended in TW(~50-54 %) and shorter in CW (~13-17 %) than those of OW. Significant differences were observed between the anatomical structures of the coniferous and deciduous species studied. Although, the greatest color differences in wet and oven-dried samples of coniferous trees were measured in CW (~15-17 %), it has been found as about 0.7-3 % in TW for deciduous species. Some differences were observed in the anatomical, optical, fiber morphological, and chemical properties of the RW for the studied wood species. Due to its higher lignin content and better physical properties, CW can be used for producing small households and hand tools, ornaments, toys, etc. It will also be appropriate for use in milling and turning work. It is recommended that, because of the lower lignin content and higher polysaccharide ratio, TW should be primarily used for the cellulose, pulp, and paper industries, where high mechanical resistance values are required. Consequently, RW formation causes some physical, chemical, mechanical, anatomical, and optical differences compared to OW in deciduous and coniferous species.
Keywords: bukovina; anatomska i kemijska struktura; fir; oak; anatomical and chemical structure; hrastovina; Forestry; borovina; SD1-669.5; jelovina; beech; pine; 15. Life on land